PROMOSI PERPUSTAKAAN UMUM KOTA PADANG - Fitria, Doris (UIN Imam Bonjol Padang, 2023)
This study describes the Promotion of Padang City Public Library. This activity can inform the promotion has been carried out, to the extent to which the development and creativity of the promotion carried out as well as techniques and breakthroughs in solving problems faced by the